[Early construction of Kennedy Library, with crane and other materials present] - P. K. Phillips::::::photographer::: (1978)
Early construction of Kennedy Library, facing west from the adjacent lawn. The crane and other materials used to complete the project are present. Also, pedestrians are on the sidewalk and cars are sitting on the street.